Universe consisting of diffusive dark fluids: thermodynamics and stability analysis - Subhayan Maity; Pritikana Bhandari; Subenoy Chakraborty (European Physical Journal C: Particles and Fields, 2019)
Abstract The present work deals with homogeneous and isotropic FLRW model of the Universe having a system of non-interacting diffusive cosmic fluids with barotropic equation of state (constant or variable equation of state parameter). Due to diffusive nature of the cosmic fluids, the divergence of the energy momentum tensor is chosen to be proportional to the diffusive current. The thermodynamic stability analysis of individual fluids is done and the stability conditions are expressed as restrictions on the equation of state parameter.